Comparing the Self-Reported Personality Disorder Traits and Childhood Traumatic Experiences Between Patients With Schizophrenia Vs. Major Depressive Disorder - Zhao, Nan; Shi, Dianhong; Huang, Juan; Chen, Qiuying; Wang, Qiang (Frontiers in Psychiatry, 2021)
Introduction: Personality disorder (PD) and childhood traumatic experience (CTE) are well- recognized risk factors for the development of schizophrenia (SZ) and major depressive disorder (MDD). The relationship between CTE and PD is extremely close, and both conditions can affect subsequent psychiatric disorders. Little is known about the differences of these factors in patients with SZ and those with MDD. Materials and Methods: A total of 1,026 outpatients participated in the study, including 533 (51.9%) with SZ and 493 (48.1%) with MDD who were sequentially sampled. The PD traits were assessed using the Personality Diagnostic Questionnaire Fourth Edition Plus (PDQ-4+). The Child Trauma Questionnaire Short Form (CTQ-SF) was used to assess childhood adversities. The scores and associations of PDQ-4+ and CTQ-SF between patients with SZ and those with MDD were compared. Results: The MDD group exhibited more PD traits and more childhood emotional neglect than the SZ group. In patients with MDD, the correlation between PD traits and CTE was significantly higher than that in patients with SZ. Patients with SZ versus those with MDD showed different PD traits and CTE. The schizotypal and antisocial PD traits, as well as sexual abuse and physical neglect CTE, were significantly related to SZ. In contrast, the borderline, narcissistic and avoidant PD traits, and emotional abuse/neglect CTE were significantly associated with MDD. Discussion: These findings indicated a robust relationship between CTE and PD traits. Moreover, patients with SZ or MDD, have different interactive patterns. Both CTE and PD traits have the potential to be premorbid risk factors that could be targeted for preventative interventions.